2015
DOI: 10.1155/2015/290128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship betweenHelicobacter pyloriInfections in Diabetic Patients and Inflammations, Metabolic Syndrome, and Complications

Abstract: Helicobacter pylori infection and diabetes mellitus are two independent common diseases. It is showed that the worsening glycemic and metabolic control increases the rates of Helicobacter pylori infections and Helicobacter pylori is shown as one of the common problems in diabetic patients with complaints of gastrointestinal diseases. In this study, we aimed to investigate the prevalence and eradication rates of Helicobacter pylori in diabetic patients and the relationship of Helicobacter pylori with the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
2
25
1
1
Order By: Relevance
“…Another 34 articles were excluded (12 were not observational studies, one did not include control group, one duplicate, and the other 20 did not report an outcome of interest). Subsequently, 18 studies including 15 cross‐sectional studies and three cohort studies involving 27 544 participants met our inclusion criteria and were included in the meta‐analysis. The search methodology is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another 34 articles were excluded (12 were not observational studies, one did not include control group, one duplicate, and the other 20 did not report an outcome of interest). Subsequently, 18 studies including 15 cross‐sectional studies and three cohort studies involving 27 544 participants met our inclusion criteria and were included in the meta‐analysis. The search methodology is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the H. pylori infection rate was significantly higher in patients with T2DM and DPG than in those without DPG, suggesting that patients with T2DM with H. pylori infection are more likely to develop the clinical manifestations of gastroparesis. The higher H. pylori infection rate in patients with diabetes may be explained by the following mechanisms:[ 7 8 9 10 11 ] (1) diabetes-related deficiencies in cellular and humoral immunity can increase H. pylori susceptibility; (2) mechanical and potential changes in the stomach due to diabetic autonomic neuropathy may lower the gastric mucosa's ability to remove bacteria; and (3) in patients with diabetes, nonenzymatic mucin glycosylation can increase salivary mucin in the gastric mucosa and thus promote the binding of H. pylori with the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In general, various studies have investigated the role of H. pylori in the pathogenesis of diabetes and its complications, but the results are inconsistent with each other. For example, some case-control studies have reported higher prevalence of H. pylori in patients with diabetes [14,15]. Also, several crosssectional studies have shown a significant statistical association between H. pylori and diabetes [3,15].…”
Section: Introductionmentioning
confidence: 99%